CLINICAL AND FUNCTIONAL CHARACTERISTICS OF PATIENTS WITH EARLY AND LATE STAGES OF DEVELOPMENT OF PROFESSIONAL SENSORINEURAL HEARING LOSS - Фунтикова, Инна Сергеевна; Потеряева, Елена Леонидовна; Смирнова, Елена Леонидовна (Medicine in Kuzbass, 2023)
To date, the mechanisms of early and late development of professional sensorineural hearing loss (PNST) remain poorly understood. Meanwhile, the analysis of associations of clinical and biochemical markers with the timing of the development of the disease allows us to justify and develop measures for effective treatment, rehabilitation and prevention. The aim of the research – to evaluate the results of clinical and functional research methods in patients with PNS with early and late stages of disease development. Materials and methods: 238 men were examined. Of these, 152 people with PNST and 86 people are workers of noise–hazardous professions without PNST. Patients with PNST were divided into two groups depending on the timing of the development of the disease. Group 1 – 58 people with early stages of disease development (work experience in noise less than 15 years), group 2 – 94 people with late stages of disease development (work experience in noise more than 15 years). The analysis of the results of clinical, functional and instrumental research methods was carried out. Results: The article presents the clinical and functional characteristics of patients with early and late stages of the development of PNST. When analyzing the clinical and functional characteristics of patients with PNST, it was found that the groups of examined patients did not differ in frequency and intensity of complaints. According to the audiological study, there were no statistical differences between these groups, as well as for the stages of sensorineural hearing loss. There were no statistically significant differences in the results of the biochemical study among the study group. Statistically significant differences were found in metabolic changes of the myocardium according to ECG data and in the frequency of occurrence of foci of gliosis according to MRI of the brain. Conclusion: The results of clinical and functional research methods showed that there were no significant differences between the groups of patients with early and late stages of the development of PNST. The presence of atherosclerotic vascular changes does not affect the timing of the formation of PNST.